Selective recognition and extraction of iodide from pure water by a tripodal selenoimidazol(ium)-based chalcogen bonding receptor - Abu S.M. Islam; Sourav Pramanik; Sahidul Mondal; Rajib Ghosh; Pradyut Ghosh (iScience, 2024)
Summary: A selenium-based tripodal chalcogen bond (ChB) donor TPI-3Se is demonstrated for the recognition and extraction of I− from 100% water medium. NMR and ITC studies with the halides reveal that the ChB donor selectively binds with the large, weakly hydrated I−. Interestingly, I− crystallizes out selectively in the presence of other halides supporting the superiority of the selective recognition of I−. The X-ray structure of the ChB-iodide complex manifests both the μ1 and μ2 coordinated interactions, which is rare in the C–Se···I chalcogen bonding. Furthermore, to validate the selective I− binding potency of TPI-3Se in pure water, comparisons are made with its hydrogen and halogen bond donor analogs. The computational analysis also provides the mode of I− recognition by TPI-3Se. Importantly, this receptor is capable of extracting I− from pure water through selenium sigma-hole and I− interaction with a high degree of efficiency (∼70%).